Figure 7 in A further study on littoral ciliates (Protozoa, Ciliophora) near King George Island, Antarctica, with description of a new genus and seven new species - Wilbert, Norbert; Song, Weibo (Zenodo, 2008)
Figure 7. Euplotes dragescoi nov. spec. after protargol impregnation. (A, B) Ventral and dorsal views of the same specimen, arrow in A marks the tiny second marginal cirrus. (C) Ventral view. AZM, adoral zone of membranelles; CC, caudal cirri; DK, dorsal kineties; FVC, frontoventral cirri; Ma, macronucleus; MC, marginal cirrus. Scale bar: 50 Mm. Published as part of Wilbert, Norbert & Song, Weibo, 2008, A further study on littoral ciliates (Protozoa, Ciliophora) near King George Island, Antarctica, with description of a new genus and seven new species, pp. 979-1012 in Journal of Natural History 42 (13-14) on page 1003, DOI:10.1080/00222930701877540, http://zenodo.org/record/5219160